Improving coherence between Irish trade and development policy from an African perspective - Matthews, Alan (Statistical and Social Inquiry Society of Ireland, 2006)
The recent Irish Trade Policy Statement devoted a whole chapter to the trade needs of developing countries (DETE, 2005). In it, the Government recognises the role that trade policy can play in providing economic development opportunities to emerging and poorer countries. It states that achieving the development dimension of the WTO Doha Development Agenda is the most effective way of realizing that ambition. The Statement confirms that Ireland wants to assist these countries to shape the outcome of the Doha process in their interest and in a way that provides the greatest opportunity for those in need.
Symposium on Ireland?s policy to Africa: trade and aid
Read before the Society, 6 April 2006
Keywords: African aid; Trade policy; Doha development agenda; 314.15